The Traffic Impact Analysis on Province Roads as Requirement for Licensing Services Provision in Building Sector - Mursito, Bambang; Kusriyah, Sri; Hafidz, Jawade (Universitas Islam Sultan Agung, 2021)
The purpose of this research is to study and analyze the impact of traffic on provincial roads as a permit requirement in the building sector by local governments based in Central Java and the solution efforts. The approach method used in this research is sociological juridical. The results of the study indicate that: the implementation of the traffic impact analysis on provincial roads encountered obstacles, among others, before the implementation of the traffic impact analysis, difficulties were the preparation of the required documents for the implementation of the traffic impact analysis, and in the implementation of the traffic impact analysis, including those related to supervision issues, not guided by the authority to analyze traffic impacts based on road status, do not understand the laws and regulations and related provisions, and lack of law enforcement.